Database of social technologies: overview - Melo Correa, Ana Paula de; Pinto, Heloisa Maria; Garcia Freitas, Carlos Cesar; Molina Freitas, Flaviane Pelloso [UNESP] (Univ Tecnologica Fed Parana-utfpr, 2020)
The present article is the result of a study that aimed the analysis of the Database of Social Technologies (DTS) For that, a descriptive research was carried out, with a qualitative approach and the use of the document analysis and interview strategies. Among the results it was evidenced that the DTS is a database that includes detailed information on Social Technologies (TS) certified under the Banco do Brazil Foundation for Social Technology Award. In all, 1354 TS have already been certified in 9 editions of the award, of which 986 are active in the DTS. These include solutions in the areas of environment, education, food, energy, housing, water resources, income and health. The area of education has the highest number of TS certified, followed by income and the environment, with 331, 208 and 157 TS projects in each one respectively.
Keywords: Social Technology; Database of Social Technologies; Disclosure Mechanism